2022
DOI: 10.3390/ijerph19052541
|View full text |Cite
|
Sign up to set email alerts
|

Attention-Deficit/Hyperactivity Disorder Symptoms, Sensation-Seeking, and Sensory Modulation Dysfunction in Substance Use Disorder: A Cross Sectional Two-Group Comparative Study

Abstract: Background: Attention-deficit/hyperactivity disorder (ADHD) and sensation-seeking, a trait characterized by risk-related behaviors, have been recognized as risk factors in substance use disorder (SUD). Though ADHD co-occurs with sensory modulation dysfunction (SMD), SMD has scarcely been explored in SUD. Thus, this study aimed to characterize ADHD symptomology, sensation-seeking, and SMD, as well as to explore their contribution to SUD likelihood. Methods: A cross sectional two-group comparative study includin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 74 publications
0
2
0
Order By: Relevance
“…Larger samples might be needed to detect group differences in ADHD related deficits ( 11 , 31 ) due to a large overlap of affected domains in ADHD and AUD ( 41 ). However, larger samples often lead to more heterogeneous groups ( 31 ).…”
Section: Discussionmentioning
confidence: 99%
“…Larger samples might be needed to detect group differences in ADHD related deficits ( 11 , 31 ) due to a large overlap of affected domains in ADHD and AUD ( 41 ). However, larger samples often lead to more heterogeneous groups ( 31 ).…”
Section: Discussionmentioning
confidence: 99%
“…Attention deficits are common in SUD patients [243][244][245][246]. In fact, research has shown that of adults presenting with SUD, 20-30% have concurrent ADHD, and 20-40% of adults diagnosed with ADHD also have a history of SUD [180,[243][244][245][246].…”
Section: Sud Induced Attention Issuesmentioning
confidence: 99%
“…Attention deficits are common in SUD patients [243][244][245][246]. In fact, research has shown that of adults presenting with SUD, 20-30% have concurrent ADHD, and 20-40% of adults diagnosed with ADHD also have a history of SUD [180,[243][244][245][246]. Therefore, the Test of Variables of Attention (TOVA), which is an attention screening test, would be useful in the diagnosis and subsequent treatment of SUD.…”
Section: Sud Induced Attention Issuesmentioning
confidence: 99%
“…Neurodivergent people frequently receive multiple diagnostic labels that overlap to explain underpinning characteristics (Kooij et al., 2019 ; Werkhoven et al., 2022 ), which has negative implications for resource management of waiting lists, risks associated with delayed pharmacological and/or nonpharmacological interventions, and difficulty managing patients’ expectations (Al‐Khudairi et al., 2019 ). When individuals do not receive the appropriate support for ADHD‐related difficulties because of delayed assessment or delayed treatment, identified risks have included increased harm to self, substance misuse, unemployment, and criminality (Assayag et al., 2022 ; Johnson et al., 2021 ). Improving the specificity and sensitivity of the diagnostic criteria for ADHD through revisions and refinements should enable the right diagnosis, at the right time.…”
mentioning
confidence: 99%